The Dirichlet problem for discontinuous perturbations of the mean curvature operator in Minkowski space - C. Bereanu; Petru Jebelean; Calin-Constantin Serban (Electronic Journal of Qualitative Theory of Differential Equations, 2015)
Using the critical point theory for convex, lower semicontinuous perturbations of locally Lipschitz functionals, we prove the solvability of the discontinuous Dirichlet problem involving the operator $u\mapstodiv \Big(\frac{\nabla u}{\sqrt{1-|\nabla u|^2}}\Big)$.